2009
DOI: 10.1111/j.1750-3841.2009.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Purple Rice Bran Extract and Its Effect on the Quality of Low‐NaCl, Phosphate‐Free Patties Made from Channel Catfish (Ictalurus punctatus) Belly Flap Meat

Abstract: Purple rice bran contains high amounts of natural antioxidants that consist of water- and lipid-soluble compounds. Hexane-insoluble and hexane-soluble fractions were separated from 100% methanolic extract from purple rice bran (RBE-HI and RBE-HS, respectively). Total anthocyanin, tannin, flavonoid, and phenolics contents were determined in those fractions, and their antioxidant capacities were evaluated by measuring 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging capability, oxygen radical absorbance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Inclusion of antioxidant food extracts has been used to limit lipid oxidation (31, 32). There was no consistent effect of the type of baked coatings upon fatty acid oxidation products.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of antioxidant food extracts has been used to limit lipid oxidation (31, 32). There was no consistent effect of the type of baked coatings upon fatty acid oxidation products.…”
Section: Discussionmentioning
confidence: 99%
“…(Del Nobile et al, 2009b). Min et al (2009) demonstrated the antimicrobial and antioxidant activity of purple rice bran extract against catfish patties.…”
Section: Fish-based Productsmentioning
confidence: 99%
“…In addition, with increasing concern about the safety of synthetic antioxidant usage (Williams and others 1999; Sasaki and others 2002), there has been increasing interest in the use of natural antioxidants from plant extracts as an alternative. Rice bran extract has been proven as an effective natural preservative in various food systems, such as meat, refined oil, and dough (Shih and Daigle 2003; Chotimarkorn and others 2008; Chotimarkorn and Silalai 2008; Min and others 2009).…”
Section: Introductionmentioning
confidence: 99%